2007
DOI: 10.1371/journal.pcbi.0030076
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Mesenchymal Condensation in a Multiscale, Discrete Stochastic Model

Abstract: Cells of the embryonic vertebrate limb in high-density culture undergo chondrogenic pattern formation, which results in the production of regularly spaced “islands” of cartilage similar to the cartilage primordia of the developing limb skeleton. The first step in this process, in vitro and in vivo, is the generation of “cell condensations,” in which the precartilage cells become more tightly packed at the sites at which cartilage will form. In this paper we describe a discrete, stochastic model for the behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 48 publications
0
56
0
Order By: Relevance
“…For example, both reaction-diffusion mechanisms [10,23] and a haptotactic mechanism [60] plausibly reproduce in vitro chondrogenesis micromass cultures, while a multitude of mechanisms, including those involving chemotaxis, mechanical traction or preferential adhesion to elongated structures, correctly reproduce in vitro blood vessel growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, both reaction-diffusion mechanisms [10,23] and a haptotactic mechanism [60] plausibly reproduce in vitro chondrogenesis micromass cultures, while a multitude of mechanisms, including those involving chemotaxis, mechanical traction or preferential adhesion to elongated structures, correctly reproduce in vitro blood vessel growth.…”
Section: Resultsmentioning
confidence: 99%
“…In the same way, eliminating the inhibitor, which the authors hypothesize is secreted by the nodules, also yielded cartilage monolayers both in silico and in vitro. Christley and coworkers refined the initial model of chondrogenesis [10], accommodating a number of new experimental observations. In contrast to the observations of Kiskowski and coworkers, 1) cell tracking measurements indicated that chondrocytes do not slow down in cartilage condensations, and 2) cell density in chondrocyte micromass cultures is constant and nodules do not deplete cells in their surroundings; cells only round up in nodules.…”
Section: Cell-based Models Of In Vitro Limb Bone Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadherin-mediated adhesion was in fact linked to GTPase-cytoskeleton signalling (Delanoe-Ayari, Al Kurdi et al 2004). Interestingly this process presents similarities with the self-organizing condensing mesenchymal cells that drive the growth of the pre-cartilagineous anlage in limb bud development through growth factor diffusion-processes and aptotaxis, although contribution from the latter seems relative (Christley, Alber et al 2007). In vitro chondrogenesis of MSC offers additional cues to dissect the pathways involved in cell shape-mediated commitment to differentiation.…”
Section: The Role Of Cell Adhesion Molecules As Active Mechanosensorsmentioning
confidence: 99%
“…Cadherin-mediated adhesion was in fact linked to GTPase-cytoskeleton signalling (Delanoe-Ayari, Al Kurdi et al 2004). Interestingly this process presents similarities with the self-organizing condensing mesenchymal cells that drive the growth of the pre-cartilagineous anlage in limb bud development through growth factor diffusion-processes and aptotaxis, although contribution from the latter seems relative (Christley, Alber et al 2007). …”
Section: The Role Of Cell Adhesion Molecules As Active Mechanosensorsmentioning
confidence: 99%